Anak Dalam Kandungan Dan Kematian Masal Dalam Fikih Mawaris - Muhammad Mahbub; Abd Ghafur (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
Mass death cases (al-halāk al-jamā‘ī) are important issues in Islamic jurisprudence because they affect the clarity of the status of both the heir and the beneficiary. In Islamic inheritance law, the presence of unborn children has a potential position as heirs if certain conditions are met, thus requiring the determination of a special inheritance share through the concept of ta‘līq al-irth. Meanwhile, mass death raises issues regarding the order of death (tartīb al-mawt) and mutual inheritance between victims, especially when it is unknown who died first. This study aims to analyze the provisions of Islamic jurisprudence related to these two issues, including the method of determining inheritance rights, dispute resolution, and legal implications for the distribution of inherited assets. Through a literature review of classical and contemporary books, this study found that Islamic jurisprudence provides a resolution mechanism through the principle of prudence (iḥtiyāṭ), the postponement of inheritance shares, and the application of the principle of al-yaqīn lā yazūlu bi al-syakk. Thus, this discussion provides a comprehensive understanding regarding the dynamics of determining inheritance rights in uncertain conditions, as well as its relevance in the modern social context.